Abnormal Functional Connectivity Between the Left Medial Superior Frontal Gyrus and Amygdala Underlying Abnormal Emotion and Premature Ejaculation: A Resting State fMRI Study - Xu, Yan; Zhang, Xing; Xiang, Ziliang; Wang, Qing; Huang, Xinfei; Liu, Tao; Yang, Zhaoxu; Chen, Yun; Xue, Jianguo; Chen, Jianhuai; Yang, Jie (Frontiers in Neuroscience, 2021)
Abstract Introduction: Premature ejaculation (PE) is a common sexual dysfunction and is found to be associated with abnormal emotion. The amygdala plays an important role in the processing of emotion. The process of ejaculation is found to be mediated by frontal-limbic neural circuits. However, the correlations between PE and emotion are still unclear. Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) data were acquired in 27 PE patients with stable emotion (SPE), 27 NPE patients and 30 healthy controls (HC). We used rs-fMRI to explore the underlying neural mechanisms in SPE, NPE and HC by measuring functional connectivity (FC). Differences of FC values among three groups were compared when choosing bilateral amygdala as regions of interest (ROI). We also explored the correlations between brain regions showing altered FC values and scores of Premature Ejaculation Diagnostic Tool (PEDT)/Eysenck Personality Inventory about neuroticism (EPQ-N) in PE group. Results: When the left amygdala was chosen as ROI, SPE group exhibited increased FC between the left medial superior frontal gyrus (SFGmed) and amygdala compared with NPE or HC group. When the right amygdala was chosen as ROI, NPE group exhibited decreased FC between the left SFGmed and right amygdala compared with HC. In addition, FC values of the left SFGmed has positive correlations with PEDT and negative correlations with EPQ-N scores in PE group. Moreover, FC values of the left superior temporal gyrus (STG) has positive correlations with EPQ-N scores in PE group. Conclusion: The increased FC values between the left SFGmed and amygdala could reflect a compensatory cortical control mechanism with the effect of stabilize emotion in the limbic regions of PE patients. Abnormal FC between these brain regions could play a critical role in the physiopathology of premature ejaculation and could help us to divide PE into more subtypes.